2017
DOI: 10.1039/c7ob00388a
|View full text |Cite|
|
Sign up to set email alerts
|

Zwitterionic pyrrolidene-phosphonates: inhibitors of the glycoside hydrolase-like phosphorylase Streptomyces coelicolor GlgEI-V279S

Abstract: We synthesized and evaluated new zwitterionic inhibitors against glycoside hydrolase-like phosphorylase Streptomyces coeticotor (Sco) GlgEI-V279S which plays a role in α-glucan biosynthesis. Sco GlgEI-V279S serves as a model enzyme for validated anti-tuberculosis (TB) target Mycobacterium tuberculosis (Mtb) GlgE. Pyrrolidine inhibitors 5 and 6 were designed based on transition state considerations and incorporate a phosphonate on the pyrrolidine moiety to expand the interaction network between the inhibitor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In both enzyme-compound structures, the interactions of the glucose moiety bound within the -2 subsite are the same as that observed in previously published Sco GlgE1-V279S/inhibitor complex structures. [50][51][52][53] However, interactions between the carbocycle moieties and the amino acid residues forming the -1 subsite differ signi cantly from each other. In the Sco GlgE1-V279S/7 complex, the interactions are similar to those observed in the substrate-bound (M1P and maltose) and substrate-mimic (MCP) complexes because the saturated carbocycle in 7 maintains the expected chair conformation.…”
Section: Kozikowski Et Al Reported That Hydrogenation Of Substitutedmentioning
confidence: 99%
See 3 more Smart Citations
“…In both enzyme-compound structures, the interactions of the glucose moiety bound within the -2 subsite are the same as that observed in previously published Sco GlgE1-V279S/inhibitor complex structures. [50][51][52][53] However, interactions between the carbocycle moieties and the amino acid residues forming the -1 subsite differ signi cantly from each other. In the Sco GlgE1-V279S/7 complex, the interactions are similar to those observed in the substrate-bound (M1P and maltose) and substrate-mimic (MCP) complexes because the saturated carbocycle in 7 maintains the expected chair conformation.…”
Section: Kozikowski Et Al Reported That Hydrogenation Of Substitutedmentioning
confidence: 99%
“…Indeed, all previously published structures of GlgE with any hexose analog have a hydroxyl at this position that interacts directly with the enzyme nucleophile. 50,52 Although speculative, such a bidentate interaction could be envisioned to stabilize a 3 H 4 or B 2,5 -TSs in the enzyme catalyzed reaction. We note some studies have suggested that reactions catalyzed by this enzyme class proceed through a 4 C 1 → 4 H 3 -TS → 1 S 3 conformational itinerary leading to a 4 C 1 enzyme-bound intermediate.…”
Section: Kozikowski Et Al Reported That Hydrogenation Of Substitutedmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years there have been sustained efforts to make a breakthrough in anti-tuberculosis drug development utilizing this key strategic information. Sucheck and co-workers developed a series of considerably effective trehalose and other glyco-conjugate-based Mtb GlgE inhibitors [217,218,219,220]. Another important chemical moiety from the classical medicinal chemistry viewpoint are the pyrazolo[1,5-a]pyrimidine and its derivatives.…”
Section: Small Particles As Antibioticsmentioning
confidence: 99%